Análise teórico-descritiva da competência em informação de gestores como fator de competitividade das indústrias de eletroeletrônicos da cidade de Garça/SP - Ottonicar, Selma Letícia Capinzaiki [UNESP] (2016)
With the rapid development of information and communication technologies, the society has the feeling that the information has become something tangible, it can be stored using different software types. However, its processing and appropriation depend on the cognitive conditions of each individual, ranging from access to the intelligent use of information to consequently be the construction of knowledge. In the business environment there is constant informational learning, since all decisions depend on information. From this perspective, the issues that guided this thesis are related to the following questions: What makes the micro and small industries organize themselves into clusters and what influence of this kind of organization, in regard to competitiveness? The manager’s information literacy is a competitive differential for the electronics industries organized into clusters? What is the relationship between the manager’s information literacy of these industries and business competitiveness? There is similarity between the manager’s information literacy characteristics in different industries in focus? The objectives are to analyze the characteristics and state of manager’s information literacy at the strategic level from micro and small industries organized into cluster, as a competitive differential. In relation to the specific objectives sought to: a) review the literature concerning micro and small industries organized into clusters; b) analyze the relationship between information literacy and competitiveness and innovation; and c) develop a case study by the electronics industries cluster in Garça City, São Paulo State, in order to identify and understand these interrelationships. As methodological procedures, we carried out a literature review which subsidize the elaboration of the theoretical reference of information management, knowledge management, clusters and information literacy; documentary research which served to prepare the characterization and historical research universe; and multiple case study, including a group of eleven (11) micro and small industries of electronics sector associated in the Commercial and Industrial Association of Garça. The results demonstrate that the information literacy is a factor of influence to obtain the business competitiveness of these industries and therefore effectively contributes to the survival of companies in the market.